Prevalence and characteristics of occupational contact dermatitis among farmers in Wongaye Gede Village, Tabanan, Bali - Sunyamurthi Wirawan, I Gde Nengah Adhilaksman; Wangsa, Putu Gde Hari (Bali Dermatology Venereology and Aesthetic Journal, 2024)
Background: Occupational contact dermatitis is a disease in the field of dermatology that arises in the work environment due to workers coming into direct contact with causative substances, be they irritants or allergens. Farmers are susceptible to various allergens or irritants when working in farming, clearing land, fertilizing, spraying, caring for, and during harvest. Epidemiological data showing contact dermatitis in Balinese farmers was still very minimal. So, based on the above background, we are interested in examining the characteristics of work-related contact dermatitis in farmers in Bali. Methods: This research method is descriptive research using a cross-sectional method that evaluates work-related contact dermatitis among farmers in Wongayo Gede Village, Penebel District, Tabanan Regency. Results: 56 farmers showed that 34 samples suffered from occupational contact dermatitis, of which 59% were men and 41% were women.  Based on the division of age groups according to WHO, it was found that youth (18-65 years) were 82%, middle-aged (66-79 years) 12%, and older adults (80-99) 6%. The highest educational background is elementary school 47%, high school 33%, and junior high school 15%. Conclusion: This research reveals that men's occupational contact dermatitis is more common. The most commonly found sample ages were young people in 18-65 years. Meanwhile, the most recent educational status of the sample was elementary school. The most common locations for skin lesions are on the upper and lower extremities.